Circulating plasmablasts/plasma cells: a potential biomarker for IgG4-related disease. Issue 1 (December 2017) - Lin, Wei; Zhang, Panpan; Chen, Hua; Chen, Yu; Yang, Hongxian; Zheng, Wenjie; Zhang, Xuan; Zhang, Fengxiao; Zhang, Wen; Lipsky, Peter
Abstract Background Immunoglobulin G4 (IgG4)-related disease (IgG4-RD) is a multisystem fibroinflammatory disease. We previously reported that a circulating cell population expressing CD19+ CD24− CD38hi was increased in patients with IgG4-RD. In this study, we aimed to document that this cell population represented circulating plasmablasts/plasma cells, to identify the detailed phenotype and gene expression profile of these IgG4-secreting plasmablasts/plasma cells, and to determine whether this B-cell lineage subset could be a biomarker in IgG4-related disease (IgG4-RD). Methods A total of 42 untreated patients with IgG4-RD were evaluated. Peripheral B-cell subsets, including CD19+ CD24− CD38hi plasmablasts/plasma cells, CD19+ CD24+ CD38− memory B cells, CD19+ CD24int CD38int naïve B cells, and CD19+ CD24hi CD38hi regulatory B cells, were assessed and sorted by flow cytometry. Microarray analysis was used to measure gene expression of circulating B-cell lineage subsets. Further characterization of CD19+ CD24− CD38hi plasmablasts/plasma cells was carried out by evaluating additional surface markers, including CD27, CD95, and human leukocyte antigen (HLA)-DR, by flow cytometric assay. In addition, various B-cell lineage subsets were cultured in vitro and IgG4 concentrations were measured by cytometric bead array. Results In untreated patients with IgG4-RD, the peripheral CD19+ CD24− CD38hi plasmablast/plasma cell subset was increased and positively correlated with serum IgG4 levels, the number of involved organs, and the IgG4-related Disease Responder Index. It decreased after treatment with glucocorticoids. Characterization of the plasmablast/plasma cell population by gene expression profiling documented a typical plasmablast/plasma cell signature with higher expression of X-box binding protein 1 and IFN regulatory factor 4, but lower expression of paired box gene 5 and B-cell lymphoma 6 protein. In addition, CD27, CD95, and HLA-DR were highly expressed on CD19+ CD24− CD38hi plasmablasts/plasma cells from patients with IgG4-RD. Furthermore, CD19+ CD24− CD38hi plasmablasts/plasma cells secreted more IgG4 than other B-cell populations. Conclusions Circulating CD19+ CD24− CD38hi plasmablasts/plasma cells are elevated in active IgG4-RD and decreased after glucocorticoid treatment. This IgG4-secreting plasmablast/plasma cell population might be a potentially useful biomarker for diagnosis and assessing response to treatment.